Introduction of Routine HIV Birth Testing in the South African National Consolidated Guidelines. Issue 6 (June 2018) - Moyo, Faith; Haeri Mazanderani, Ahmad; Barron, Peter; Bhardwaj, Sanjana; Goga, Ameena Ebrahim; Pillay, Yogan; Sherman, Gayle G.
Abstract : Background: South Africa represents the first high-burden setting to introduce routine virologic testing at birth within its early infant diagnosis program, implemented in June 2015. National HIV birth testing coverage, intrauterine transmission rates and case rates for the first year since introduction of universal birth testing are reported. Methods: HIV polymerase chain reaction (PCR) test data from June 2015 to May 2016 were extracted from the National Health Laboratory Service's central data repository by year, month, age, result and geographic location. Birth testing was defined as all HIV PCR tests performed at <7 days of life; coverage as the proportion of all HIV-exposed neonates born who were tested at birth; estimated intrauterine transmission rate as the percentage of HIV PCR positive tests in HIV-exposed neonates tested and case rates as the number of HIV PCR positive tests per 100, 000 total live births. Results: Between June 2015 and May 2016, the South African national monthly birth testing coverage increased from 39% (8636 tests) to 93% (20, 479 tests). During this period, the number of positive tests at birth increased from 114 to 234 per month, equating to a national intrauterine transmission rate of 1.1% and a birth case rate of 247 per 100, 000 live births. Conclusions: Universal birth testing for all HIV-exposed neonates is rapidly being achieved in South Africa, facilitating earlier detection of intrauterine infected neonates. However, the successful linkage into care of HIV-infected neonates and their treatment outcomes remain to be assessed.